The Emerald Atlas - Stephens, John 1972- (New York : Alfred A. Knopf, 2011)
After years of moving from one orphanage to another following their parents' disappearance, Kate, Michael, and Emma learn that they have special powers, a prophesied quest to find a magical book, and a fearsome enemy.
Keywords: Siblings -- Fiction; Magic -- Fiction; Space and time -- Fiction; Identity (Psychology) -- Fiction; Monsters -- Fiction; Prophecies -- Fiction; Books and reading -- Fiction